Cultural shocks: understanding the impact on international students' academic journey at Yogyakarta, Indonesia - Ahmed, Touheed; Shahzeb, Shahzeb (Universitas Negeri Yogyakarta, 2024)
This study explores the experiences of international students who face cultural shock when starting higher education in Indonesia. Cultural shock manifests itself in a variety of ways, including changes in food, societal norms, behaviour, language, and religion, which cause students to experience stress, anxiety, and depression. The study investigates the coping mechanisms of the students, which include maintaining communication with locals, friends and family, engaging with Indonesian peers and immersing themselves in local culture. Despite initial difficulties, students gradually adjust to their new academic environment, aided by language proficiency, supportive university communities, and cultural assimilation within the curriculum. The findings emphasise the importance of predeparture education in terms of study programmes and their global implications, as well as fostering receptivity to diverse cultures and understanding cultural differences in order to facilitate effective adaptation and academic success abroad. Limitations include the subjective nature of experiences and the need for further investigation of specific cultural adaptation strategies. The recommendations include providing comprehensive support services for international students and incorporating cultural education into academic curricula.